UNNOTICED IN CHILDHOOD, DISABLING IN ADULTHOOD: A PROGRESSIVE BUT TREATABLE DISEASE…. Issue 11 (9th October 2013) - Murdoch, Sheena; Davidson, Amy; Galloway, Peter; Joseph, Robin; Selvarajah, Johann
Abstract : A 64 year old Caucasian man presented with subtle cognitive decline of uncertain duration and a six month history of progressive difficulty mobilising with falls. He reported increasing stiffness in both legs, followed by both arms. He reported some visual blurring, difficulty concentrating and poor working memory. His medical background was unremarkable. There was no family history of neurological disease. His birth and early development were normal but he was academically below average throughout schooling. He was a retired factory worker. He smoked and drank little alcohol. Neurological examination demonstrated progressive spasticity in all four limbs, most prominently in the lower limbs, with hyper–reflexia, movement–induced clonus and spasms. There was global cognitive dysfunction, with particular difficulties in concentration, registration, recall, visuo–spatial skills and praxis. Addenbrooke's cognitive examination score was 59. MRI brain showed bilateral, symmetrical, confluent, predominantly posterior, subcortical and deep white matter high signal change on T2/FLAIR with global cerebral atrophy. Spinal imaging showed moderate cervical canal stenosis with no cord signal change. Evoked potentials were normal. Nerve conduction and EMG studies showed no evidence of peripheral nerve disease or myopathy. CSF was acellular, biochemically normal and sterile. No bands were detected. Blood and urine screens were performed for metabolic, toxic, inflammatory and infective causes of the clinical picture. An amino acid chromatogram detected hyperphenylalaninaemia with normal tyrosine, confirmed on blood spot, indicating a diagnosis of phenylketonuria (PKU). A restricted protein diet was commenced and the patient continues to show evidence of cognitive and motor recovery. Video illustrations of the patient will be available for presentation. PKU is an autosomal recessive defect of phenylalanine hydroxylation affecting 1 in 10, 000 in the UK. It is usually diagnosed pre–symptomatically with a newborn screening programme introduced in 1969, after the birth of our patient. If not detected on screening, PKU usually presents in childhood with seizures and learning disability. However, the clinical spectrum is broad and PKU presenting in mid to late adulthood is rare but recognised 1–3. Variable clinical recovery is possible with dietary restriction, although compliance is difficult. This case serves to remind us that inborn metabolic errors do not always present to paediatricians and that 'long–standing' white matter abnormalities should be scrutinised according to clinical context. Finally, we will speculate on the genetic substrate for the striking variation in disease phenotype, the aetiology and pathogenesis of brain injury, and the mechanisms of decompensation leading to late clinical presentation.